Oxime reactivators and their in vivo and in vitro effects on nicotinic receptors - Soukup, O; Krůšek, J; Kaniaková, M; Kumar, U K; Oz, M; Jun, D; Fusek, J; Kuča, K; Tobin, G (Physiological research, 2011)
Current treatment of organophosphorus poisoning, resulting in overstimulation and desensitization of muscarinic and nicotinic receptors by acetylcholine (ACh), consists of the administration of atropine and oxime reactivators. However, no versatile oxime reactivator has been developed yet and some mortality still remains after application of standard atropine treatment, probably due to its lack of antinicotinic action. In our study, we focused on the interesting non-acetylcholinesterase property of oximes, i.e. antinicotinic effect of reactivators. Two standard reactivators (HI-6, obidoxime) and two new compounds (K027 and K203) were chosen for in vitro (patch clamp) and in vivo (nerve-evoked muscle contraction) testings. Both examinations showed antinicotinic effects of the reactivators. In vitro inhibition of acetylcholine-evoked currents by obidoxime, HI-6 and K203 was equivalent while K027 was less potent. Similar order of potency was observed by the in vivo examinations. We thus confirm previous in vitro results, which describe antinicotinic effects of oxime reactivators, and furthermore, we show in vivo antagonism of oxime reactivators exerted by the inhibition of ACh effect on the nicotinic receptor in the neuromuscular junction. Taking together, the effects of tested oxime reactivators indicate an antagonism on both embryonic and adult form of the muscle nicotinic receptors.
Keywords: nikotinové receptory; Male; potkani Sprague-Dawley; Obidoxime Chloride; vztah mezi dávkou a účinkem léčiva; Oximes; mužské pohlaví; Nicotinic Antagonists; Receptors, Nicotinic; Cholinesterase Reactivators; Pyridinium Compounds; obidoxim chlorid; krysa rodu Rattus; Animals; pyridinové sloučeniny; nikotinoví antagonisté; zvířata; Rats; reaktivátory cholinesterasy; oximy; Dose-Response Relationship, Drug; Rats, Sprague-Dawley